Factores de sostenibilidad de las ventas en la empresa Altec de la ciudad de Babahoyo - Miranda Jara, Jesus Micheld (2020)
This research allows to analyze the sales sustainability factors of the company Altec S.A. For it, the marketing and commercialization sub line was used and also analytical, descriptive, bibliographic research methods that permit to get the objective set; the information was collected through an interview with the company's administrative staff and a survey questionnaire comprising ten questions that was developed in collaboration with regular customers of Altec S.A. , that allowed to identify and argue from the criteria of authors elements and characteristics that focuses on the low level of sales mainly due to the lack of a strategic alignment, evidencing flaws as inadequate coordination of activities, lack of training for its personnel in charge, lack of assignment of the necessary tools, blocking the proper development of processes, preventing activities from being carried out in a more organized and agile way, which leads to the identification of possible solutions that mitigate the impact of said problem as much as possible.